The first thing we do, let's deregulate all the lawyers - Winston, Clifford 1952- (Brookings Institution Press, 2011)
"Proposes deregulating entry into the legal profession to open up competition among and improve innovation by lawyers, reduce social costs of high legal fees, and make more efficient use of the nation's labor resources, while lowering legal costs and providing consumers with a wider range of legal services"--Provided by publisher.